Mutually exclusive expression of DLX2 and DLX5/6 is associated with the metastatic potential of the human breast cancer cell line MDA-MB-231 - Mirisola Valentina; Emionite Laura; Gitton Yorick; Astigiano Simonetta; Morini Monica; Levi Giovanni; Barbieri Ottavia (BMC Cancer, 2010)
Abstract Background The DLX gene family encodes for homeobox transcription factors involved in the control of morphogenesis and tissue homeostasis. Their expression can be regulated by Endothelin1 (ET1), a peptide associated with breast cancer invasive phenotype. Deregulation of DLX gene expression was found in human solid tumors and hematologic malignancies. In particular, DLX4 overexpression represents a possible prognostic marker in ovarian cancer. We have investigated the role of DLX genes in human breast cancer progression. Methods MDA-MB-231 human breast carcinoma cells were grown in vitro or injected in nude mice, either subcutaneously, to mimic primary tumor growth, or intravenously, to mimic metastatic spreading. Expression of DLX2, DLX5 and DLX6 was assessed in cultured cells, either treated or not with ET1, tumors and metastases by RT-PCR. In situ hybridization was used to confirm DLX gene expression in primary tumors and in lung and bone metastases. The expression of DLX2 and DLX5 was evaluated in 408 primary human breast cancers examining the GSE1456 and GSE3494 microarray datasets. Kaplan-Meier estimates for disease-free survival were calculated for the patients grouped on the basis of DLX2/DLX5 expression. Results Before injection, or after subcutaneous growth, MDA-MB-231 cells expressed DLX2 but neither DLX5 nor DLX6. Instead, in bone and lung metastases resulting from intravenous injection we detected expression of DLX5/6 but not of DLX2, suggesting that DLX5/6 are activated during metastasis formation, and that their expression is alternative to that of DLX2. The in vitro treatment of MDA-MB-231 cells with ET1, resulted in switch from DLX2 to DLX5 expression. By data mining in microarray datasets we found that expression of DLX2 occurred in 21.6% of patients, and was significantly correlated with prolonged disease-free survival and reduced incidence of relapse. Instead, DLX5 was expressed in a small subset of cases, 2.2% of total, displaying reduced disease-free survival and high incidence of relapse which was, however, non-significantly different from the other groups due to the small size of the DLX+ cohort. In all cases, we found mutually exclusive expression of DLX2 and DLX5. Conclusions Our studies indicate that DLX genes are involved in human breast cancer progression, and that DLX2 and DLX5 genes might serve as prognostic markers.